Units in families of totally complex algebraic number fields - L. Ya. Vulakh (International Journal of Mathematics and Mathematical Sciences)
Multidimensional continued fraction algorithms associated with GLn(ℤk), where ℤk is the ring of integers of an imaginary quadratic field K, are introduced and applied to find systems of fundamental units in families of totally complex algebraic number fields of degrees four, six, and eight.